The mechanosensitive lncRNA Neat1 promotes osteoblast function through paraspeckle-dependent Smurf1 mRNA retention - Liu, Caizhi; Gao, Xingcheng; Li, Yuheng; Sun, Weijia; Xu, Youjia; Tan, Yingjun; Du, Ruikai; Zhong, Guohui; Zhao, Dingsheng; Liu, Zizhong; Jin, Xiaoyan; Zhao, Yinlong; et al. (Bone Research, 2022)
Mechanical stimulation plays an important role in bone remodeling. Exercise-induced mechanical loading enhances bone strength, whereas mechanical unloading leads to bone loss. Increasing evidence has demonstrated that long noncoding RNAs (lncRNAs) play key roles in diverse biological, physiological and pathological contexts. However, the roles of lncRNAs in mechanotransduction and their relationships with bone formation remain unknown. In this study, we screened mechanosensing lncRNAs in osteoblasts and identified Neat1 , the most clearly decreased lncRNA under simulated microgravity. Of note, not only Neat1 expression but also the specific paraspeckle structure formed by Neat1 was sensitive to different mechanical stimulations, which were closely associated with osteoblast function. Paraspeckles exhibited small punctate aggregates under simulated microgravity and elongated prolate or larger irregular structures under mechanical loading. Neat1 knockout mice displayed disrupted bone formation, impaired bone structure and strength, and reduced bone mass. Neat1 deficiency in osteoblasts reduced the response of osteoblasts to mechanical stimulation. In vivo, Neat1 knockout in mice weakened the bone phenotypes in response to mechanical loading and hindlimb unloading stimulation. Mechanistically, paraspeckles promoted nuclear retention of E3 ubiquitin ligase Smurf1 mRNA and downregulation of their translation, thus inhibiting ubiquitination-mediated degradation of the osteoblast master transcription factor Runx2, a Smurf1 target. Our study revealed that Neat1 plays an essential role in osteoblast function under mechanical stimulation, which provides a paradigm for the function of the lncRNA-assembled structure in response to mechanical stimulation and offers a therapeutic strategy for long-term spaceflight- or bedrest-induced bone loss and age-related osteoporosis.